The smell hits you first - Ndoro, Tariro (Rhodes University, Faculty of Humanities, Institute for the Study of English in Africa, 2016)
This collection of poems and prose poems is a record of my life, from growing up in the small town of Bindura in Zimbabwe to landing in the small town of Grahamstown in South Africa. It is a story of dislocation: physical, emotional, and political. It is a story about borders and boundaries; although not rich, I was raised among the rich; although not white, I spent a considerable part of my childhood in white spaces. These fragments are told through the voice of my younger self and also retrospectively by my adult self. Two important influences on my style and my struggle to write about my identity have been Woman Hollering Creek by Latino American author Sandra Cisneros and Citizen: An American Lyric by US poet Claudia Rankine.
Keywords: Uncatalogued